A novel electrochemical sensor based on β-cyclodextrin functionalized carbon nanosheets@carbon nanotubes for sensitive detection of bactericide carbendazim in apple juice. (1st August 2022) - Liu, Runqiang; Li, Bo; Li, Fang; Dubovyk, Volodymyr; Chang, Yuqi; Li, Dongdong; Ding, Kunjie; Ran, Qiwen; Wang, Guifang; Zhao, Hongyuan
Highlights: A simple and green strategy to prepare the β-CD/CNS@CNT nanocomposite. β-CD/CNS@CNT can make full use of their respective advantages of β-CD, CNS, and CNT. The β-CD/CNS@CNT/GCE sensor showed a low limit of detection (LOD) of 9.4 nM. The pretty practical feasibility was achieved for the detection of CBZ in apple juice. Abstract: Carbendazim (CBZ) abuse always causes the over-standard of pesticide residues in agricultural products, which has adverse effects on human health. Herein, a novel electrochemical sensor was firstly fabricated based on the β-cyclodextrin (β-CD) functionalized carbon nanosheets@carbon nanotubes (CNS@CNT) for the CBZ determination. CNS@CNT combined large surface area of CNS and excellent electrical conductivity of CNT, which significantly enhanced the electrocatalytic performance. Moreover, β-CD possessed excellent host-gest supramolecular recognition ability, which could improve the selective recognition and enrichment capability of CBZ. Thanks to the synergistic interaction of CNS@CNT and β-CD, the β-CD/CNS@CNT/GCE sensor exhibited a low limit of detection of 9.4 nM in the linear CBZ concentration range of 0.03–30 μM. The fabricated sensor presented favorable stability, high sensitivity (30.86 μA μM −1 cm −2 ), and reliable reproducibility (RSD = 3.6%). Especially, the β-CD/CNS@CNT/GCE sensor could show pretty practical feasibility for the detection of CBZ in apple juice with recoveries of 97.1%-99.4%.